Methods for Accurate Assessment of Myofiber Maturity During Skeletal Muscle Regeneration - Yoshimoto, Yuki; Ikemoto-Uezumi, Madoka; Hitachi, Keisuke; Fukada, So-ichiro; Uezumi, Akiyoshi (Frontiers in Cell and Developmental Biology, 2020)
Adult skeletal muscle has a remarkable ability to regenerate. Regeneration of mature muscle fibers is dependent on muscle stem cells called satellite cells. Although they are normally in a quiescent state, satellite cells are rapidly activated after injury, and subsequently proliferate and differentiate to make new muscle fibers. Myogenesis is a highly orchestrated biological process and has been extensively studied, and therefore many parameters that can precisely evaluate regenerating events have been established. However, in some cases, it is necessary to evaluate the completion of regeneration rather than ongoing regeneration. In this study, we establish methods for assessing the myofiber maturation during muscle regeneration. By carefully comparing expression patterns of several muscle regeneration-related genes, we found that expression of Myozenin (Myoz1 and Myoz3), Troponin I (Tnni2) and Dystrophin (Dmd) is gradually increased as muscle regeneration proceeds. In contrast, commonly used regeneration markers such as Myh3 and Myh8 are transiently upregulated after muscle injury but their expression decreases as regeneration progresses. Intriguingly, upregulation of Myoz1, Myoz3 and Tnni2 cannot be achieved in cultured myotubes, indicating that these markers are excellent indicators to assess myofiber maturity. We also show that analyzing re-expression of Myoz1 and dystrophin in individual fiber during regeneration enables accurate assessment of myofiber maturity at the single-myofiber level. Together, our study provides valuable methods that are useful in evaluating muscle regeneration and the efficacy of therapeutic strategies for muscle diseases.